PERANAN KOORDINASI CAMAT DALAM MENUNJANG KEBERHASILAN PEMBANGUNAN DI WILAYAH KECAMATAN LANGOWAN BARAT - RANTUNG, FRANDY ALVANDO; Pangkey, Masje; Rompas, Sonny (Sam Ratulangi University, 2015)
Abstract: success in establishing a town. What's in the coordination and supervision of the sector. it is, of course,interfere with the process of running programs that have been in the plan. Weak coordination system in the Sub-DistrictGovernment apparatus into a problem and need to examine again. and from the observations of the author of one of thedistricts in the Regency of Minahasa Langowan Barat subdistrict, precisely Not optimally cordinated by the Governmentapparatus. The purpose of this research was to determine the role of the head of the coordination support the success ofthe Western development in district LangowanDeparting from the problem and research objectives, the type of research that is in use is a kind of qualitative research,with observation data retrieval techniques, interviews, library studies and documentation.The results of discussion demonstrating that: head of coordination in the West, already Langowan goes well with goodand is in compliance with duty as head of the subdistrict. The apparatus is still lacking resources this is apparent in thelevel of education is still at domination by the , it graduates have also affected the management of the existingadministration in district of Western Langowan supporting facilities in the Office District is still pretty minimal. This canbe seen from the lack of vehicle service, so the process of work particularly in the program directly into the fieldsufficiently slow also facilities such as computers, and the internet at the Office of the district that has not been adequate.Referring to the conclusion above then suggested the role of head of coordination is currently well underway for thatrequire consistency in the conduct of all existing programs. Camat presumably always act firmly but could also considerand hear the right advice from the staff officers, so harmony and harmony in a joint task. In the study permit andpresumably training program to the entire Government apparatus in district West langowan So that in carrying out allduties and job bias is more effective the addition of means of transport is very important in that the mobilization andemployment particularly work directly into the countryside this is certainly requires an adequate means of transport to bebiased work goes well, the addition of computer and ancillary administration tool is also a very important thing,considering so much of his Government duties that require computer and technology tool tools supporting the other.Keywords: The Role Of The Head Of Coordination